2008
DOI: 10.1111/j.1538-7836.2007.02824.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factors and the protein C system as determinants of thrombin generation in a normal population

Abstract: The lag time, ETP and peak height of thrombin generation depend on the levels of multiple coagulation factors and inhibitors. The specific assay determinants vary with the experimental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
202
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(242 citation statements)
references
References 32 publications
30
202
4
1
Order By: Relevance
“…3 Conceding the fact that no race matched controls were included in this study, a marked in vitro resistance to thrombomodulin was detected (as compared to historical controls) 7 indicating functional protein C resistance, which is in accordance with reported reduced protein C and S levels in SCD. 10 In interpreting these data several factors need to be considered.…”
supporting
confidence: 66%
“…3 Conceding the fact that no race matched controls were included in this study, a marked in vitro resistance to thrombomodulin was detected (as compared to historical controls) 7 indicating functional protein C resistance, which is in accordance with reported reduced protein C and S levels in SCD. 10 In interpreting these data several factors need to be considered.…”
supporting
confidence: 66%
“…In contrast, there is a linear relationship between increasing levels of factor II and increased thrombin generation [32,33]. Finally, a recently published study has shown that, following activation with a high concentration of tissue factor, prothrombin is amongst the main determinants of total thrombin generation [34]. The available evidence therefore indicates that accumulation of factor II could be the primary determinant of thrombotic risk associated with frequent doses of PCC.…”
Section: Pccs and Thrombotic Risk: Pathogenesismentioning
confidence: 99%
“…As an example, the European external assessment Three kinds of plasmas were chosen to cover the whole spectrum of thrombin generation measuring range, markedly hypocoagulable, normocoagulable and highly hypercoagulable, as compared to data obtained in healthy subjects under similar conditions [18,20]. For practical purposes it was decided for defective coagulation to supplement normal plasma with heparin.…”
Section: Discussionmentioning
confidence: 99%